In-situ diagnostics of hydrocarbon dusty plasmas using quantum cascade laser absorption spectroscopy and mass spectrometry. (14th July 2014) - Ouaras, K.; Delacqua, L. Colina; Lombardi, G.; Röpcke, J.; Wartel, M.; Bonnin, X.; Redolfi, M.; Hassouni, K.
Abstract : The formation of carbon nanoparticles in low pressure magnetized H2 /CH4 and H2 /C2 H2 plasmas is investigated using infrared quantum cascade laser absorption, mass spectrometry, and electrostatic probe measurements. Results showed that dust formation is correlated to the presence of a significant amount of large positively charged hydrocarbon ions. Large negative ions or neutral hydrocarbon were not observed. These results, along with a qualitative comparison of diffusion and reaction characteristic, suggest that a positive ion may contribute to the growth of nanoparticles in hydrocarbon magnetized plasmas.